Implementation of Android-Based Indonesian Syntactic Game - Syahrin, Alvi; Khair, Ummul; Rismayanti, Rismayanti (Journal of Computer Science and Informatics Engineering, 2023)
The implementation of Indonesian Syntax Game based on Android is a project aimed at developing a gaming application designed to help users improve their understanding and mastery of Indonesian grammar interactively through gaming. This application utilizes the Android platform as a medium of presentation and provides various levels of challenges with different levels of difficulty. Each level is arranged with different grammar content, allowing users to learn progressively and structured. In its implementation, this application uses active learning methods and constructivism, emphasizing on enjoyable and interactive learning experiences. The application testing results show that this Indonesian Syntax Game based on Android is effective in improving users' understanding of Indonesian grammar, and it has received positive responses from users in terms of interface and gaming content.